Land Tenancy and Non-contractible Investment in Rural Pakistan - Jacoby, Hanan G.; Mansuri, Ghazala (2012)
Commitment failure lies at the core of incomplete contract theory, yet its quantitative significance has rarely been assessed. Using detailed plot-level data from rural Pakistan, we find that non-contractible investment is underprovided on tenanted land, even after controlling for the endogeneity of leasing decisions. Our evidence also indicates that moral hazard in investment effort alone cannot explain this inefficiency. Instead, imperfect commitment appears to be the driving mechanism, since even plots taken on fixed rent contracts where all the rent is paid upfront receive lower investment than owner-cultivated plots. We further show that a considerable portion of the variation in tenancy duration, and hence in the security of tenure, is due to heterogeneity across landlords. One interpretation of this finding is that landlord reputation is important in mitigating hold-up.